Juegos lúdicos y su influencia en el desarrollo de la motricidad gruesa en niños de 4 años de la Unidad Educativa Francisco Huerta Rendón - Cáceres Guapi, Nathaly Gabriela (2023)
Playful games play a fundamental role in the development of gross motor skills in 4-year-old children. These games are essential to stimulate gross motor skills. The application of recreational activities within the educational field is essential; since, they create favorable environments so that students can interrelate with each other, generating harmonious and productive environments. The main objective of this case study is to determine how recreational scenarios influence the development of gross motor skills in 4-year-old children from the Francisco Huerta Rendón Educational Unit. The research design is non-experimental. The types of research used were documentary and field. The population was made up of 81 4-year-old children who study at the aforementioned establishment. The study sample was selected through non-probabilistic sampling, consisting of 30 students and 2 teachers. The results of the research allowed us to conclude that recreational games generate an important impact on the development of 4-year-old children, since they are essential for physical development, helping to stimulate gross and fine motor skills. In addition, it contributes to cognitive, emotional and social development, which is essential for future challenges and learning. Therefore, it is important that the teachers of the Francisco Huerta Rendón Educational Unit diversify and carry out a wide variety of recreational activities that stimulate the physical development and gross motor skills of 4-year-old children. This may include outdoor games, team games, climbing, jumping, running, and balance activities.